Management of oral and maxillofacial trauma during the first wave of the COVID-19 pandemic in the United Kingdom. Issue 8 (October 2021) - Puglia, F.A.; Hills, A.; Dawoud, B.; Magennis, P.; Chiu, G.A.; ,; Adams, Aidan; Ahmed, Ayesha; Aiman, Huma; Al-Harbawee, Aya; Alderson, Lucy; Allison, Jack; et al.
Abstract: We assess the effect of coronavirus disease 2019 (COVID-19) on UK oral and maxillofacial (OMF) trauma services and patient treatment during the first wave of the pandemic. From 1 April 2020 until 31 July 2020, OMF surgery units in the UK were invited to prospectively record all patients presenting with OMF trauma. Information included clinical presentation, mechanism of injury, how it was managed, and whether or not treatment included surgery. Participants were also asked to compare the patient's care with the treatment that would normally have been given before the crisis. Twenty-nine units across the UK contributed with 2, 229 entries. The most common aetiology was mechanical fall (39%). The most common injuries were soft tissue wounds (52%) and, for hard tissues, mandibular fractures (13%). Of 876 facial fractures, 79 patients' treatment differed from what would have been normal pre-COVID, and 33 had their treatment deferred. Therefore the care of 112 (14%) patients was at variance with normal practice because of COVID restrictions. The pattern of OMFS injuries changed during the first COVID-19 lockdown. For the majority, best practice and delivery of quality trauma care continued despite the on-going operational challenges, and only a small proportion of patients had changes to their treatment. The lessons learnt from the first wave, combined with adequate resources and preoperative testing of patients, should allow those facial injuries in the second wave to receive best-practice care.